Love: an important dimension in marital research and therapy - Riehl-Emde, Astrid; Thomas, Volker; Willi, Jürg (Family process, 2003)
How do men and women describe and assess their relationship? What themes are decisive for its quality and stability? To answer such questions, we investigated a random sample of 204 married couples (reference sample), and 31 married couples undergoing psychotherapy (clinical sample) using a newly developed questionnaire. The participating couples were asked to evaluate a total of 19 themes with respect to their importance for the couple's connectedness. Although only rarely directly addressed in couple therapy and investigated in couple research, the theme "Love" proved to be the decisive factor for quality and stability. The results of the present study, therefore, indicate that "Love" should be investigated more thoroughly in couple research and included more actively in diagnostic and therapeutic procedures.
Gesehen am 22.03.2021